Biological control of Tetranychus urticae Koch (Acari: Tetranychidae) with Phytoseiulus persimilis Athias-Henriot (Acari: Phytoseiidae) on roses in the Sabana of Bogota - DE CARVALHO FRANCA, SORAYA; DE VISE, RAF (Revista Colombiana de Entomología, 1996)
The present and tries to contribute to the knowledge on the habits of Phytoseiulus persimilis under the conditions of the Sabana of Bogota through the evaluation of three different levels of this species (5, 15 and 45 predators per plant) for the control of Tetranychus urticae in roses, seven monthold cv. Madame Delbard. The plots were infested with T urticae to obtain a level of approximately 40 spider mites (eggs + mobile forms) / leaflet before the release of P persimilis. Analysis of the data from the maintenance layer of the plants showed a tendency toward control as of week 5. However, in the treatment 5 predators/plant, a significant population increase was observed prior to its control. By week 8, averages of the treatments 15 and 45 predators/plants were near the O pest population. Results from the production layer of the plants showed that in all treatments the pest mite moved upwards. On the other hand, the upwards movement of the predators was also observed with an ensuing control of the pest. In all treatments, a good level of control was observed by week IO. The authors suggest that this predator is a good candidate for the control of T urticae under the conditions of the Sabana of Bogota. The initial level of infestation by T urticae was found to be too high for rapid control by P persimilis. As the treatments 15 and 45 predators/plant obtained similar results, it is assumed that a little over 15 predators/plant is sufficient to obtain the same results.